Effect of maturation level on normative specific-agility performance metrics and their fitness predictors in soccer players aged 11-18 years - Sellami, M.; Makni, E.; Moalla, W.; Tarwneh, R.; Elloumi, M. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background In sports sciences, normative data serve as standards for specific physical performance attributes, enhancing talent identification within a specific population. The aim of this study was to provide standard data for Agility-15 m, Ball-15 m tests, and skill index, considering maturation level, specifically age at peak height velocity (PHV). The study also investigated the relationship between relative performances in these tests and anthropometrics, jumping (squat jump [SJ], countermovement jump [CMJ]), and sprinting abilities (S-5 m, S-10 m, S-20 m, S-30 m) in young soccer players.